For whom the bell tolls: London's Iraq and Afghanistan Memorial 1990-2015. Issue 3 (19th May 2020) - Grady, Kate
Abstract: Following the recent turn to materiality in international legal scholarship, this article considers London's Iraq and Afghanistan Memorial 1990-2015. By examining the memorial's politics in respect of death quantification, gender, and lawfulness, the article reveals international law's roles in contributing to the conditions of possibility from which the wars in Iraq and Afghanistan arose.